2016
DOI: 10.1159/000444173
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Underweight Prevalence Trends in Children from Romania - Pooled Analysis of Cross-Sectional Studies between 2006 and 2015

Abstract: Aim: High-quality national representative data on obesity in Romanian children are needed to shape public health policies. To providea unified data landscape on national prevalence, trends and other factors associated with underweight, overweight, and obesity in Romanian children aged 6-19 years, across the last decade (2006-2015). Methods: Using a common protocol, we selected published and unpublished studies that measured Romanian children in schools between 2006 and 2015. Children's BMI was classified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 34 publications
8
40
1
Order By: Relevance
“…The association between gender and overweight/obesity is inconsistent in the literature. A number of studies reported higher prevalence in girls , some found higher estimates in boys and others reported similar prevalence estimates . In a study involving Australian school children, obesity prevalence did not differ between boys and girls in primary school children; however, substantial gender differences were observed among adolescents in high school suggesting age–gender interactions .…”
Section: Discussionmentioning
confidence: 93%
“…The association between gender and overweight/obesity is inconsistent in the literature. A number of studies reported higher prevalence in girls , some found higher estimates in boys and others reported similar prevalence estimates . In a study involving Australian school children, obesity prevalence did not differ between boys and girls in primary school children; however, substantial gender differences were observed among adolescents in high school suggesting age–gender interactions .…”
Section: Discussionmentioning
confidence: 93%
“…Contrary to other studies, although point estimates for childhood obesity and overweight were generally higher in females than in males, no significant gender difference in childhood obesity or overweight was found in the current meta-analysis. Reports on the gender difference in childhood obesity or overweight prevalence are inconsistent; some studies report higher prevalence in males [64,65], others report higher prevalence in females [66]while some report no gender difference in childhood obesity or overweight prevalence [67]. In a similar study involving a meta-analysis of obesity and overweight among school-going children in Africa, no gender difference in obesity or overweight prevalence was reported [56].…”
Section: Discussionmentioning
confidence: 99%
“…Two methods were used for obtaining informed consent from the participants in our study [25] . The first method used a "passive consent" or "opt out" method, where parents were fully informed about all study procedures through a school information meeting.…”
Section: Ethical Considerationsmentioning
confidence: 99%